Description of one new species of genus Ramila Moore, 1867 (Lepidoptera, Crambidae, Schoenobiinae) from Indian Sunderbans with a revised key to the Indian species. (2nd October 2017) - Biswas, Olive; Shah, Suresh Kr.; Modak, Biplob Kr.; Mitra, Bulganin
Abstract: One new species of genus Ramila (named Ramila sunderbanensis sp. nov.) is described and illustrated from two male specimens collected from the mangroves of Sunderban Biosphere Reserve, India. The new species is characterised by oval-shaped saccus, gnathos smaller (2/3rd) than uncus of the male genitalia and forewing without any discocellular lunule. http://www.zoobank.org/urn:lsid:zoobank.org:pub:C72A38EB-475D-4DCD-A16D-EDDC930FB4D6